Tuition Tax Credits A Review of Current Proposals and Their Potential Impacts - Picus, Larry; Northwest Regional Educational Lab., Portland, OR. Northwest Center for State Educational Policy Studies ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1981)
The Packwood/Moynihan/Roth Tuition Tax Relief Act of 1981 and the nearly 20 other tuition tax credit bills introduced since the beginning of the current session of Congress are intended to provide tax credits for a portion of the tuition paid for private education. Two major studies attempting to determine the impacts of passage of a tuition tax credit law were published by Martha J. Jacobs and the Congressional Budget Office. Both studies found that tuition tax credits would lead to disproportionate distribution of benefits--favoring white, middle-to-upper income, and Southern families--and could result in a significant loss of revenue to the federal government. (Author/PGD)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Educational Finance; Educational Legislation; Elementary Secondary Education; Federal Legislation; Private School Aid; Tax Credits; Tuition; Opinion Papers; Information Analyses